2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-2.14611
|View full text |Cite
|
Sign up to set email alerts
|

Human microbiota and effectiveness of cancer chemotherapy

Abstract: Summary. This review presents up-to-date information on the effects of microbiota on the individual chemotherapy sensitivity in cancer treatment. Recent studies have shown that a fine balance between the intestinal microbiota and the immune system is crucial for maintaining an efficacy of cancer chemotherapy. A number of antitumor drugs have complex mechanisms of action involving not only direct effects but also the activity of the intestinal microbiota and the immune system. A unique combination of these fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In fact, a good balance between the gut microbiota and the immune system is a decisive key to maintaining the effectiveness of anticancer chemotherapy [ 90 ]. Elimination of the microbiota by administering broad-spectrum antibiotics alters host response, since genes that promote cancer metabolism and progression are upregulated, with simultaneous downregulation in inflammatory, phagocytic, and antigen presentation pathways [ 91 ].…”
Section: Elective Therapy In Lung Cancer and The Role Of The Microbiotamentioning
confidence: 99%
“…In fact, a good balance between the gut microbiota and the immune system is a decisive key to maintaining the effectiveness of anticancer chemotherapy [ 90 ]. Elimination of the microbiota by administering broad-spectrum antibiotics alters host response, since genes that promote cancer metabolism and progression are upregulated, with simultaneous downregulation in inflammatory, phagocytic, and antigen presentation pathways [ 91 ].…”
Section: Elective Therapy In Lung Cancer and The Role Of The Microbiotamentioning
confidence: 99%
“…The sequences obtained are mapped onto reference genomes to obtain the relative quantification of taxa, from which the microbial diversity is derived, or subjected to de novo assembly for the identification of new phyla [41]. The Metagenomics of the Human Intestinal Tract and the Human Microbiome Project have provided the most integrated view of humanassociated microbes: 2172 species have been isolated in human gut microbiota [42], and a healthy gut microbiota is mainly dominated by Bacteroidetes and Firmicutes, while Proteobacteria, Verrucomicrobia, Actinobacteria and several other phyla are present in smaller proportions [43].…”
Section: The Human Gut Microbiotamentioning
confidence: 99%
“…These include the polyphenolic anthocyanins (AC, 23, 24) and their active metabolite protocatechuic acid Peiffer et al, 2014), as well as the active metabolites of ellagic acid, the urolithins Kujawska & Jodynis-Liebert, 2020). In parallel with these findings, other groups have demonstrated that ones microbiome may affect their response to chemotherapy including colonic, breast, and pancreatic cancers (Khodavirdipour, Jamshidi, Nejad, Zandi, & Zarean, 2020;Shvets, Lukianova, & Chekhun, 2020;Zhang, Gao, Li, Wang, & Liu, 2020). This relationship however appears complex as some chemotherapeutics target the cancer cells while also negatively affecting the host's microbiome (Campbell, Gagnon, & Rubin, 2019;Domalaon et al, 2019;Flórez, Sierra, Ruas-Madiedo, & Mayo, 2016, Nicholson et al, 2012.…”
Section: Introductionmentioning
confidence: 96%